How do we distinguish termite stone lines from artefact horizons? A challenge for geoarchaeology in tropical Australia. Issue 2 (3rd October 2019) - Smith, M. A.; Ward, Ingrid; Moffat, Ian
Abstract: Can we distinguish stone lines created by termite bioturbation from genuine artefact horizons? This is a challenge for field archaeology and geoarchaeology in northern Australia, where termites are abundant. We review published data to (a) present a model of the evolution of stone lines and (b) develop guidelines for recognizing these bioturbation products in archaeological contexts. In case studies, we examine Madjedbebe and Nauwalabila, two sites in northern Australia. The early occupation levels at these sites are pivotal to ideas about initial human occupation of the Australian landmass but there are claims these are unrecognized stone lines. Our assessment is that neither Madjedbebe nor Nauwalabila contain termite stone lines, although both sites may have complex geomorphic and taphonomic histories.